Nitrogen management in Basmati rice under variable irrigation regimes: Implications on rice yield, and nutrient concentrations - KUMARI, KAVITA; DASS, ANCHAL; SINGH, RAJIV K.; DHAR, SHIVA; SUDHISHRI, S.; DAS, T.K.; DARSHAN (Journal of Soil and Water Conservation, 2024)
A field experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhi, India during the kharif 2021 and 2022, to determine the effect of nitrogen (N) rate, sources, and varying irrigation regimes on basmati rice (Oryza sativa L.). The experiment consisted of 12-combinations of three irrigation regimes viz., irrigation at 1, 3 and 6 days after drying of surface water (I1DADSW, I3DADSW and I6DADSW) allotted to main-plots and four N-management options including 100% recommended dose of N: (NRDN); 75% RDN+ 2 nano urea (NU) sprays (N75%RDN+NU); 50% RDN + NU spray (N50%RDN+NU) and the control plot (No- N) allotted to sub-plots, all set in a split-plot design replicated thrice. Across the years, implementing delayed irrigation in I6DADSW reduced the grain yield by 13–19% over I3DADSW and by 23–28% compared to I1DADSW. Moreover, I1DADSW recorded greater agronomic efficiency (25.3, 25.9 kg grain/kg N applied) as well as grain and straw N, P and K contents compared to other treatments. Among N treatments, NRDN led to increment of 14.5 and 41.5% in grain yield over N50%RDN+NU and control (N0), respectively, though it was statistically at par with N75%RDN+NU. In addition, NRDN and N75%RDN+NU superiorly performed also in terms of grain and straw N acquisition over N50%RDN+NU and control. Grain P was not affected significantly by N treatments, though their interaction with irrigation produced a significant effect on the same. Grain K content exhibited its highest values in treatment, where N was omitted, might be attributed to higher consumption of basal K applied and low biomass production due to N-stress. Further, agronomic efficiency (AE) reduced with increments in N-dose and followed the trend as N50%RDN+NU> N75%RDN+NU> NRDN during both years. The maximum AE (29.5 kg grain/kg N applied) was exhibited by the crop that was irrigated I1DADSW and fertilized with N50%RDN+NU.